Dynamics of charged and their radiation field - Spohn, Herbert (Cambridge University Press, 2004)
This self-contained and systematic introduction to classical electron theory and nonrelativistic quantum electrodynamics covers the interaction between charges and the Maxwell field, with particular focus on the derivation of radiative friction. It provides a coherent presentation with emphasis on radiation phenomena and relaxation to the ground state, space-adiabatic limit, effective mass and g-factor, and removal of the ultraviolet cut-off. The book is suitable for graduates and researchers in mathematical physics, particle physics and applied mathematics.